The Comparison of PCR Kits for the Detection of Erythrocytic Parasites on Filter Paper - Tao, Zhi-yong; Zhang, Pei-yi; Zhang, Lu; Li, Chun-cao; Hu, Rui; Zhu, Han-wu; Zhou, Bei; Wu, Kai; Li, Ling-xu; Yao, Da-wei; Cao, Yu-jie; Wang, Dao-jin; et al. (Journal of tropical medicine, 2022)
Dried blood spot (DBS) based PCR was considered an inexpensive and feasible method for detecting pathogens in the blood. The DBS carrier filter paper and PCR kits are crucial for accurate diagnosis. We evaluated 4 types of filter papers and 20 PCR kits for DBS samples. The PCR detecting Plasmodium results showed that the minimum detection limit of the 4 filter papers was 1 × 102 parasites/μL, and the positive rates of 20 PCR kits ranged from 0% to 100%. PCR results were satisfactory for detecting Plasmodium falciparum (P. falciparum) and Plasmodium. vivax (P. vivax) in archived DBS samples and Babesia gibsoni (B. gibsoni) in fresh pet DBS samples. Our results provided a useful reference for the detection of blood pathogens with DBS samples and direct PCR, especially for screening the cost-efficacy combination of filter paper and PCR kit in resource-limited areas.